ATL internals : working with ATL 8 - Tavares, Chris (Addison-Wesley, 2006)
The Classic Guide to ATL-Now Updated for ATL 8 and Visual Studio 2005 Four leading Windows programming experts systematically reveal ATL's inner workings, explaining not just how ATL works, but why it works the way it does. Client-side developers will master ATL's resources for windowing, COM control, MFC integration, web service proxy generation, and more. Server-side programmers will discover ATL's full COM server and object services, and its extensive support for high-throughput, high-concurrency web applications, and services. Every Windows developer will learn powerful ways to increase flexibility, reduce overhead, and maximize transparency and control. - Discover ATL's internals through diagrams, example code, and internal ATL implementation code - Walk through wizards that simplify ATL usage in common applications - Master string handling in C++, COM, and ATL - Leverage ATL smart types, including CComPtr, CComQIPtr, CComBSTR, and CComVariant - Understand and choose the right options for implementing IUnknown - Create glue code that exposes COM objects from COM servers - Use canned interface implementations to support object persistence, COM collections, enumerators, and connection points - Build standalone applications and UI components with ATL window classes and controls - Use ATL Server to develop web applications that run on Microsoft IIS.